The Influence Of The Availability Of Alcoholic Beverages On The Drinking Habits Of Adolescents - Zulkaidah, Zulkaidah; Shaluhiyah, Zahroh; Mustafa, Syamsulhuda Budi (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2023)
Alcoholic beverages are all types of drinks that contain ethanol (C2H5OH). Consumption of alcohol hurts the health and psychological health of the drinker, even the impact of environmental damage. Alcoholic beverages among youth are increasing along with the development of information and ease of transportation. Ease of access to alcoholic beverages is thought to be one of the factors increasing consumption of alcoholic beverages in youth. According to the KPAI, supervision of the circulation of alcoholic beverages is still weak, so young people who are not old enough can access these drinks. The study aimed to determine how much influence the availability of alcoholic beverages had on the drinking habits of junior and senior high school youth in Kelurahan A in Merauke Regency. The research method used was Correlative Descriptive Research on junior high and high school youth in Kelurahan A in Merauke Regency. The results of this study indicate that based on the results of bivariate analysis using the results of the chi-square (x²) statistical test, with a CI = 95% (α = 5%), a value of p = 0.000 is obtained. This suggests that the availability of alcoholic beverages affects the drinking habits of junior and senior high school youth in Kelurahan A in Merauke Regency because it has a p-value <0.05. The results of the linear regression analysis test showed that the variable that had the most influence on the habit of drinking alcoholic beverages in junior high and high school youth was the availability of alcohol because it had the highest odds ratio of 2.184. This means that the availability of alcohol has a probability of 2.